Iran-Taliban Cooperation: New Dimension in Afghan Conflict? - Abdul Basit (2016)
Following the killing of the Taliban Chief Akhtar Mansoor, Taliban’s relationship, and cooperation with the Shia majority Iran has emerged as a new dimension of the Afghan conflict. Cooperation between the two old-foes defies historical geopolitical and geo-sectarian trends.